2003
DOI: 10.1007/bf02976881
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin gallate prevents autoimmune diabetes induced by multiple low doses of streptozotocin in mice

Abstract: Cytokines produced by immune cells infiltrating pancreatic islets have been incriminated as important mediators of beta-cell destruction in insulin-dependent diabetes mellitus. In non insulin-dependent diabetes, cytokines are also associated with impaired beta-cell function in high glucose condition. By the screening of various natural products blocking beta-cell destruction, we have recently found that epigallocatechin gallate (EGCG) can prevent the in vitro destruction of RINm5F cell, an insulinoma cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(83 citation statements)
references
References 19 publications
5
75
0
3
Order By: Relevance
“…EGCG has been shown to be involved in regulation of a variety of metabolic processes and has been used as an anti-obesity reagent in animal models and in humans (3)(4)(5)(6). Although its effectiveness in the treatment of human diabetes has not been established, EGCG has been shown in rodents to be effective in preventing the development of Type I diabetes and treatment of Type II diabetes (7,8). The mechanism of EGCG regulation of metabolism remains to be established although a variety of different roles for EGCG have been suggested.…”
Section: Epigallocatechin-3-gallate (Egcg)mentioning
confidence: 99%
“…EGCG has been shown to be involved in regulation of a variety of metabolic processes and has been used as an anti-obesity reagent in animal models and in humans (3)(4)(5)(6). Although its effectiveness in the treatment of human diabetes has not been established, EGCG has been shown in rodents to be effective in preventing the development of Type I diabetes and treatment of Type II diabetes (7,8). The mechanism of EGCG regulation of metabolism remains to be established although a variety of different roles for EGCG have been suggested.…”
Section: Epigallocatechin-3-gallate (Egcg)mentioning
confidence: 99%
“…In particular, green tea (Ϫ)-epigallocatechin gallate (EGCG; Fig. 1), the majority of GTC, lowers the incidence of streptozotocin-induced diabetes (42) and reduces body weight, body fat, and blood levels of glucose and lipid in leptin receptor-defective obese rats (20,21). In addition, EGCG protects pancreatic cells (42), enhances insulin activity (2), represses hepatic glucose production (51), reduces food uptake and absorption (20,27), stimulates thermogenesis (13) and lipid excretion (27), and modulates insulin-leptin endocrine systems (20).…”
Section: Resistin (Rstn) Is a Cysteine-rich Polypeptide Hormonementioning
confidence: 99%
“…Thus, EGCG protects pancreatic cells (Song et al, 2003), enhances insulin activity (Dhawan et al, 2002), represses hepatic glucose production (Waltner-Law et al, 2002), reduces food uptake and absorption (Kao et al, 2000), stimulates thermogenesis by increasing the uncoupling protein 2 (UCP2) and lipid excretion (Dulloo et al, 1999;Liao, 2001), and modulates insulin-leptin endocrine systems (Kao et al, 2000). Moreover, EGCG inhibits the sodium-dependent glucose transporter (Kobayashi et al, 2000) and represses various enzymes related to lipid metabolism, such as acetyl-CoA carboxylase, fatty acid synthase, pancreatic lipase, gastric lipase, and lipooxygenase (Liao, 2001;Wang & Tian, 2001) as well as lipolytic genes such as hormone sensitive lipase (HSL) and adipose triglyceride lipase (ATGL) in adipose tissue (Lee et al, 2009).…”
Section: Green Teamentioning
confidence: 96%
“…Moreover, several "in vivo" studies demonstrated that green tea extracts or EGCG dietary supplementation decreased both body and adipose tissue weights (Park et al, 2011;Choo, 2003;Hasegawa et al, 2003), improved insulin sensitivity and glucose tolerance (Cao et al, 2007;Serisier et al, 2008) and had beneficial effects on prevention of hypertension (Ihm et al, 2009) and modulation of plasma cholesterol (Bursill et al, 2007), conditions linked to metabolic syndrome. In addition, it lowers the incidence of streptozotocin-induced diabetes (Song et al, 2003) and reduces body weight, body fat, and blood levels of glucose and lipid in leptin receptor-defective obese rats (Kao et al, 2000).…”
Section: Green Teamentioning
confidence: 99%